IMPLIKASI MOTIVASI BELAJAR SISWA TERHADAP MATA PELAJARAN AGAMA HINDU DI TENGAH HEGEMONI BUDAYA INDUSTRI DI SMAN 8 DENPASAR - Siswadi, Gede Agus (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2024)
This research aims to analyse the implications of students learning motivation on Hinduism subjects at SMAN 8 Denpasar, especially in the context of the increasingly strong hegemony of industrial culture. The method used in this research is qualitative method. The results showed that students' learning motivation has a significant influence on academic achievement in Hinduism subject. Students who have high motivation tend to participate more actively in learning and have a better understanding of Hindu values. On the other hand, the hegemonic industrial culture that dominates students‘ social environment has the potential to reduce students’ interest and attention to religious studies. The implication of this study confirms the importance of increasing learning motivation through relevant and contextual approaches, so that students can integrate Hindu values in students' daily lives, despite being affected by industrial culture. It is hoped that the results of this study can be a reference for educators and schools in designing more effective and interesting learning strategies to increase student motivation.